(untitled) (Revista "Boletín el Conuco", 2020)
Research addressed a study on dropout and student retention in the context of the program of accounting public of the Universidad de los Llanos, the purpose of the study is to determine the different factors affecting this problem to the inside of the programme, in relation to the methodology applied in the same. His contribution focuses on the contributions that make the information obtained, in order to search the student dropout rate decrease, improve retention and the quality of the training. The theoretical and conceptual framework that supports the research is based on the following theories: models of analysis of student attrition in higher education, social inequality and education, which is to examine all incidents which may affect a student’s decision to abandon its university stage from a perspective of social, economic, family. Likewise, the research focused on an analysis of the curriculum offered by the program, using statistical data provided by the program of Unillanista student retention, PREU, identifying the population of students in accounting, from the first until the last six months in the last five cohorts, this is accomplished through a study of a mixed (qualitative and quantitative) from the analysis and interpretation of aspects of the object of study, this process makes it possible to carry out an evaluation of permanence and retention report.